EFFECTS OF SEED INOCULATION WITH Azospirillum brasilense AND NITROGEN DOSE ON OIL CONTENT OF CORN GRAINS - Dias, Vanderlan Carneiro; Peluzio, Joênes Mucci; Lima, Maria Dilma de (REVISTA DE AGRICULTURA, 2019)
ABSTRACT Due to its high economical importance and the need of high amounts of nitrogen fertilizer, the corn crop demands further and deeper studies on biological nitrogen fixation trough bacterium Azospirillum brasilense. Therefore, this study aimed at assessing influence of inoculation of three different genotypes (Orion, A1 Bandeirante and AG-1051) with such bacterium in association with cover application of five different nitrogen doses on percentage oil content in the grains. Data were subjected to ANOVA and means compared by Tukey test at 5%. The inoculation of A. brasilense, with or without nitrogen fertilization, has promoted oil content increase in the grains. Orion genotype presented the greatest increase with the bacterium inoculation, as well as it was the most productive at the lowest nitrogen dosages assessed. High temperatures favored the increase in the oil content in the grains. Keywords: Zea mays, inoculation, biological fixation, oil EFEITOS DA INOCULAÇÃO COM Azospirillum brasilense E DOSE DE NITROGÊNIO SOBRE O TEOR DE ÓLEO DE MILHO RESUMO Devido à sua grande importância econômica e necessidade de fertilizantes nitrogenados, a cultura do milho exige estudos mais aprofundados sobre a fixação biológica do nitrogênio pela bactéria Azospirillum brasilense. Portanto, este estudo teve como objetivo avaliar a influência da inoculação de três diferentes genótipos (Orion, A1 Bandeirante e AG-1051) com essa bactéria em associação com a aplicação de cinco diferentes doses de nitrogênio no teor percentual de óleo nos grãos. Os dados foram submetidos à ANOVA e as médias comparadas pelo teste de Tukey a 5%. A inoculação de A. brasilense, com ou sem adubação nitrogenada, promoveu aumento do teor de óleo nos grãos. O genótipo Orion apresentou o maior aumento com a inoculação da bactéria, bem como o mais produtivo nas menores dosagens de nitrogênio avaliadas. As temperaturas altas favorecem ou aumentam o teor de óleo nos grãos. Palavras-chave: Zea mays, inoculação, fixação biológica, óleo